Historiography of the novel Min Hikayati Jaddati by Suhayr al-Qalamawy: a study of new historicism - Syarofina, Mahjatin Nabilah; Zawawi, Moh. (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
The nineteenth century was distinguished by a period of considerable turbulence and strife between Europe and the Middle East. One such event was the Battle of Alexandria and the subsequent outbreak of the Mahdi Revolution in Sudan. Suhayr al-Qalamawy's historical novel Min Hikayati Jaddati is the object of this research. The novel recounts the experience of a grandmother attempting to ascertain the whereabouts of her three children, who had enlisted in the Egyptian army under the command of Urabi in the conflict against the British. This research examines the economic and political representations in the novel Min Hikayati Jaddati through the lens of new historicism. The research method employed is a qualitative narrative with a new historicism approach model. The findings of this research relate to the strategy of the British forces in paralyzing the Urabi forces in Tal Kabir, which killed many people, thus affecting the political factors at that time, namely the change of power from the hands of Ismail Pasha to Khedive Tawfiq. The economic impact that arose after the war was the increase in food prices, which resulted in the instability of the country's economy and the rise in poverty.